Acute Tension-Type Headaches Are Associated with Impaired Cognitive Function and More Negative Mood - Smith, Andrew Paul (Frontiers in Neurology, 2016)
Background/Aims: Research has shown that migraine is often associated with memory problems. There have, however, been few studies of tension type headache (TTH) and cognition. People who report frequent headaches often report high levels of negative affect. However, less is known about the acute effects of tension type headache on mood. To address these gaps in our knowledge, two studies examined the effects of acute TTH on cognitive performance and mood. Methods: Both studies involved one group of participants completing a battery of tasks when they had a TTH and when they had no headache. Another group (the control) was headache free on both occasions. Duration of the headache was greater than 30 minutes and less than 4 hours. In the “no headache” condition the participants were headache free for at least 24 hours. In the first study 12 participants (6 with TTH, 6 controls) completed a computerised battery measuring mood and aspects of cognition. In the second study 22 participants (7 TTH, 5 after TTH and10 controls) completed paper and pencil mood and cognitive tasks. Results: In the first study having a headache was associated with an increase in negative affect both before and after the tasks. Three performance tasks showed impairments when the participants had headaches: logical reasoning was slower and less accurate; retrieval from semantic memory was slower; and reaction times in the categoric search task were slower. Results from the second study confirmed the global increase in negative affect when the person has a TTH. The results confirmed the impairments in the logical reasoning and semantic processing tasks and also showed that those with a TTH had greater psychomotor slowing and were more easily distracted. Effects did not continue after the headache had gone. Conclusions: Two small-scale studies have shown that TTH is associated with negative affect and impaired cognitive function. It is now of interest to determine whether OTC treatment can remove these effects.